2013
DOI: 10.1007/s11427-013-4575-0
|View full text |Cite
|
Sign up to set email alerts
|

Spectrin: Structure, function and disease

Abstract: Spectrin is a large, cytoskeletal, and heterodimeric protein composed of modular structure of and subunits, it typically contains 106 contiguous amino acid sequence motifs called "spectrin repeats". Spectrin is crucial for maintaining the stability and structure of the cell membrane and the shape of a cell. Moreover, it contributes to diverse cell functions such as cell adhesion, cell spreading, and the cell cycle. Mutations of spectrin lead to various human diseases such as hereditary hemolytic anemia, ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 70 publications
0
70
0
Order By: Relevance
“…Spectrins are cytoskeletal, heterodimeric proteins composed of alpha and beta subunits, with important roles in maintaining the stability of the cell membrane, promoting adhesion and spreading, regulating Golgi and vesicular transport, and controlling cell cycle progression (5861). Moreover, β III -spectrin can enhance cell survival through maintenance of the Golgi apparatus and regulation of cell surface receptor vesicular transport, including glutamate receptors (6062).…”
Section: Resultsmentioning
confidence: 99%
“…Spectrins are cytoskeletal, heterodimeric proteins composed of alpha and beta subunits, with important roles in maintaining the stability of the cell membrane, promoting adhesion and spreading, regulating Golgi and vesicular transport, and controlling cell cycle progression (5861). Moreover, β III -spectrin can enhance cell survival through maintenance of the Golgi apparatus and regulation of cell surface receptor vesicular transport, including glutamate receptors (6062).…”
Section: Resultsmentioning
confidence: 99%
“…Sptbn1 was a member of the OFM, and of the two genes, BMD was altered in mice with perturbed Sptbn1 expression. SPTBN1 is a molecular scaffolding protein that links the actin cytoskeleton to the plasma membrane (Zhang et al, 2013b). Through this role, it has been implicated in the regulation of cell shape, adhesion and TGF-β signaling (Zhang et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…SPTBN1 plays an important role in the determination of cell shape, the arrangement of transmembrane proteins and the organization of organelles [35]. A recent report showed that by regulating the Wnt inhibitor kallistatin, loss of SPTBN1 activates Wnt signaling and promotes progression of hepatocellular carcinoma and Wnt signaling [36].…”
Section: Resultsmentioning
confidence: 99%